A Genome-Wide Analysis Reveals Stress and Hormone Responsive Patterns of TIFY Family Genes in Brassica rapa - Saha, Gopal; Park, Jong-In; Kayum, Md. Abdul; Nou, Ill-Sup (Frontiers in Plant Science, 2016)
The TIFY family is a plant-specific group of proteins with a diversity of functions and includes four subfamilies, viz. ZML, TIFY, PPD and JASMONATE ZIM-domain (JAZ) proteins. TIFY family members, particularly JAZ subfamily proteins, play roles in biological processes such as development and stress and hormone responses in Arabidopsis, rice, chickpea and grape. However, there is no information about this family in any Brassica crop. This study identifies 36 TIFY genes in Brassica rapa, an economically important crop species in the Brassicaceae. An extensive in silico analysis of phylogenetic grouping, protein motif organization and intron-exon distribution confirmed that there are four subfamilies of BrTIFY proteins. Out of 36 BrTIFY genes, we identified 21 in the JAZ subfamily, 7 in the TIFY subfamily, 6 in ZML and 2 in PPD. Extensive expression profiling of 21 BrTIFY JAZs in various tissues, especially in floral organs and at different flower growth stages revealed constitutive expression patterns, which suggest that BrTIFY JAZ genes are important during growth and development of B. rapa flowers. A protein interaction network analysis also pointed to association of these proteins with fertility and defense processes of B. rapa. Using a low temperature-treated whole-genome microarray data set, most of the JAZ genes were found to have variable transcript abundance between the contrasting inbred lines Chiifu and Kenshin of B. rapa. Subsequently, the expression of all 21 BrTIFY JAZs in response to cold stress was characterized in the same two lines via qPCR, demonstrating that nine genes were up-regulated. Importantly, the BrTIFY JAZs showed strong and differential expression upon JA treatment, pointing to their probable involvement in JA-mediated growth regulatory functions, especially during flower development and stress responses. Additionally, BrTIFY JAZs were induced in response to salt, drought, Fusarium, ABA, and SA treatments, and six genes (BrTIFY3a, 3b, 6a, 9a, 9b and 9c) were identified to have co-responsive expression patterns. The extensive annotation and transcriptome profiling reported in this study will be useful for understanding the involvement of TIFY genes in stress resistance and different developmental functions, which ultimately provides the basis for functional characterization and exploitation of the candidate TIFY